Meaningful Online Connections during Covid-19: Reflections on Using Arts-Based Approaches in Social Work Practice. Issue 5 (11th November 2022) - MacAulay, Debbie; Levy, Susan
Abstract : This paper offers reflections on an organic turn to the arts as a means of connecting and working with children and young people online during the Covid-19 pandemic. Lockdowns during the pandemic required social work practitioners, students, and social care staff to find innovative and creative ways of engaging with people. Online delivery of services presents both challenges and opportunities for communicating and building relationships. The arts, currently underutilised in social work, is one way to open up opportunities, and provide a 'way in' to the lives of people who use services. This paper draws on reflections from a student social worker based in Scotland, UK, on how a turn to the arts provided an effective means to connect with and understand the children and young people she was supporting. The paper first explores some of the benefits of using the arts in social work practice; second, it introduces online arts-based approaches used during the Covid-19 pandemic; and concludes by encouraging readers to adopt and adapt the approaches introduced in the paper to integrate arts-based approaches into social work.